1993
DOI: 10.1093/ije/22.3.428
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Intervention: The Coronary Risk Factor Study (CORIS)

Abstract: The Coronary Risk Factor Study (CORIS) examined the feasibility and effectiveness of a multifactorial community intervention programme to reduce coronary heart disease (CHD) risk factor levels. Three Afrikaner communities were surveyed before and after a 4-year intervention in two of the communities, the third serving as a control (C). Intervention was primarily by small mass media (low-intensity intervention, LII) or by small mass media plus interpersonal intervention to high-risk individuals (high-intensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 0 publications
0
39
0
Order By: Relevance
“…In addition, hypertension decreased in the intervention group by 21%, and this reduction was greater for women than men. Others have found similar reductions in blood pressure 100 or no change at all. 96 Change in cholesterol levels.…”
Section: Community Settingsmentioning
confidence: 80%
See 1 more Smart Citation
“…In addition, hypertension decreased in the intervention group by 21%, and this reduction was greater for women than men. Others have found similar reductions in blood pressure 100 or no change at all. 96 Change in cholesterol levels.…”
Section: Community Settingsmentioning
confidence: 80%
“…[94][95][96][97][98][99][100][101] Because the type of interventions varied, it is not possible to say which strategy worked best in the community. None were designed to study women primarily, but all included women and reported findings based on gender.…”
Section: Interventions Targeting Multiple Risk Factorsmentioning
confidence: 99%
“…[15][16][17] Finally, the strata were divided according to 3 levels of total cholesterol: Ͻ5.18 mmol/L (200 mg/dL), 5.18 to 7.25 mmol/L (200 to 280 mg/dL), and Ն7.25 mmol/L (280 mg/dL). 18,19 The proportion in each stratum of the cohort reflected the results of the 1998 South African Demographic and Health Survey 12 for age, sex, smoking status, and blood pressure. The distributions of cholesterol and diabetes mellitus were stratified with mean values according to sex, because few data exist to determine their relationship to the other risk factors.…”
Section: South Africa Cvd Risk Stratificationmentioning
confidence: 99%
“…As the same impact was not observed in the small-scale rural area studies within the study period, it may be preferable to investigate the effects of intervention across society (18). South Africa (19), America-Missouri (20) and Sweden (21) studies are successful examples of such an approach.…”
Section: Discussionmentioning
confidence: 91%